Insolvency Risks in Islamic Banks: Lessons from Comparative Case Studies of Failed Institutions - Nor, Ahmad Hidayat bin Md; Muneeza, Aishath (International Journal of Islamic Economics and Governance, 2025)
This study investigates the causes of insolvency in Islamic banks (IBs) through a qualitative multiple-case analysis of failed Islamic financial institutions (IFIs) in Turkey, Jordan, and South Africa. The selected cases İhlas Finans (IF), Islamic Bank Limited (IBL), Islamic Investment House (IIH), and Islamic National Bank (INB) are examined to identify key governance, regulatory, and Shariah-related weaknesses that contributed to their collapse. Data were collected from secondary sources, including regulatory reports, court records, and academic studies, and analyzed using thematic and comparative approaches. The findings reveal that inadequate governance, absence of comprehensive insolvency and recovery frameworks, and weak Shariah governance were central causes of institutional failure. Conflicts between national laws and Shariah principles further compounded the insolvency risks. The study contributes to the literature by providing a cross-jurisdictional understanding of insolvency risks in Islamic banking and proposing the need for structured resolution mechanisms aligned with Shariah principles. Policy recommendations are offered to enhance regulatory supervision, strengthen Shariah governance, and improve crisis preparedness within the Islamic banking sector.